Marijuana Use among Pregnant Women with Mental Health-Related Disabilities. Issue 1 (2nd January 2020) - Kitsantas, Panagiota; Krall, Jenna R.; Ramos, Yesenia; Pollack, Anna Z.; Kornides, Melanie
Abstract: This study was designed to examine prenatal marijuana use in pregnant women with disabilities related to mental health. Almost one-third (28.8%) of 3805 pregnant women reported a mental health-related disability, and 4% reported past 30-day marijuana use. Women with a moderate/severe mental health-related disability had higher adjusted-odds of marijuana use (OR: 2.05, 95% CI: 1.33, 3.16) than did their counterparts. Women were significantly more likely to use marijuana in the first than in a later trimester. Given potential adverse health outcomes associated with prenatal marijuana use, providers should screen pregnant women with mental health-related disabilities for marijuana use, and intervene to prevent and reduce/eliminate use.